GidA, a tRNA Modification Enzyme, Contributes to the Growth, and Virulence of Streptococcus suis Serotype 2 - Gao, Ting; Tan, Meifang; Liu, Wanquan; Zhang, Chunyan; Zhang, Tengfei; Zheng, Linlin; Zhu, Jiawen; Li, Lu; Zhou, Rui (Frontiers in Cellular and Infection Microbiology, 2016)
Glucose-inhibited division protein (GidA), is a tRNA modification enzyme functioning together with MnmE in the addition of a carboxymethylaminomethyl group to position 5 of the anticodon wobble uridine of tRNA. Here, we report a GidA homologue from a Chinese isolate SC-19 of the zoonotic Streptococcus suis serotype 2 (SS2). gidA disruption led to a defective growth, increased capsule thickness, and reduced hemolytic activity. Moreover, the gidA deletion mutant (ΔgidA) displayed reduced mortality and bacterial loads in mice, reduced ability of adhesion to and invasion in epithelial cells, and increased sensitivity to phagocytosis. The iTRAQ analysis identified 372 differentially expressed (182 up- and 190 down-regulated) proteins in ΔgidA and SC-19. Numerous DNA replication, cell division and virulence associated proteins were downregulated, whereas many capsule synthesis enzymes were upregulated by gidA disruption. This is consistent with the phenotypes of the mutant. Thus, GidA is a translational regulator that plays an important role in the growth, cell division, capsule biosynthesis, and virulence of SS2. Our findings provide new insight into the regulatory function of GidA in bacterial pathogens.